Exosome‐derived miR‐210 involved in resistance to osimertinib and epithelial–mesenchymal transition in EGFR mutant non‐small cell lung cancer cells. Issue 11 (3rd May 2021) - Hisakane, Kakeru; Seike, Masahiro; Sugano, Teppei; Yoshikawa, Akiko; Matsuda, Kuniko; Takano, Natsuki; Takahashi, Satoshi; Noro, Rintaro; Gemma, Akihiko
Abstract: Background: Osimertinib is a third‐generation epidermal growth factor receptor‐tyrosine kinase inhibitor (EGFR‐TKI) approved for the treatment of patients with EGFR ‐mutant non‐small cell lung cancer (NSCLC). However, the mechanisms of acquired drug resistance to osimertinib have not as yet been clarified. Exosomes and microRNAs (miRNAs) are involved in carcinogenesis and drug resistance in human cancers. Methods: We used previously established osimertinib‐resistant HCC827 (HCC827‐OR) and PC‐9 (PC‐9‐OR) cells. We evaluated the profiles of exosomal miRNA associated with resistance to osimertinib in EGFR ‐mutant NSCLC cells. Results: Epithelial–mesenchymal transition (EMT) phenomenon was observed in HCC827‐OR and PC‐9‐OR cells. Microarray and quantitative reverse transcription‐polymerase chain reaction analysis revealed that miR‐210‐3p was co‐upregulated in exosomes isolated from HCC827‐OR and PC‐9‐OR cells compared with those isolated from parental HCC827 and PC‐9 cells. HCC827‐OR cell‐derived exosomes induced EMT changes and resistance to osimertinib in HCC827 cells. Subsequently, the induction of miR‐210‐3p directly promoted the EMT phenomenon and resistance to osimertinib in HCC827 cells. Conclusions: Exosomal miR‐210‐3p may play a crucial role in resistance to osimertinib in the tumor microenvironment of EGFR ‐mutant NSCLC. Abstract : MiR‐210‐3p was overexpressed in exosomes isolated from osimertinib‐resistant cells. Exosomes derived from osimertinib‐resistant cells induced EMT changes and drug resistance in osimertinib‐sensitive cells. Induction of miR‐210‐3p directly promoted the EMT phenomenon and drug resistance in osimertinib‐sensitive cells.